Analysis and comparison of the trends in burden of spinal cord injury in China and worldwide from 1990 to 2021: an analysis of the global burden of disease study 2021 - Qin, Hao; Diao, Yuhang; Hao, Mingyu; Wang, Zhitan; Xie, Minghao; Hu, Xiaojun; Zhu, Tao (Frontiers in Public Health, 2025)
BackgroundSpinal cord injury (SCI) is a globally prevalent neurological condition, often resulting in motor, sensory, and autonomic dysfunctions that lead to permanent disability. However, outdated epidemiological data hinder the development and implementation of effective public health policies. This study aimed to examine and compare trends in the burden of spinal cord injury—specifically incidence, prevalence, and years lived with disability (YLD)—in China and worldwide from 1990 to 2021, and to project these trends over the next 15 years.MethodsThis study analyzed the characteristics of the SCI burden in China and globally, examining changes in incidence, prevalence, and years lived with disability (YLD) using open data from the Global Burden of Disease database covering 1990 to 2021. Additionally, Joinpoint and age-period-cohort (APC) analyses were conducted to provide insights into the epidemiological characteristics of the SCI burden. The autoregressive integrated moving average (ARIMA) model was then applied to project SCI trends for the next 15 years.ResultsIn 2021, the prevalence and incidence of SCI in China reached 2,766,277 and 99,363 cases, respectively, marking increases of 63.27 and 43.27% since 1990. From 1990 to 2021, the age-standardized prevalence rate (ASPR) of SCI decreased significantly, with an estimated annual percentage change (EAPC) of −0.34 (95% CI: −0.60 to-0.07). At the gender level, SCI prevalence and incidence were higher in men than in women. Joinpoint analysis revealed a significant decrease in the APC of the age-standardized incidence rate (ASIR) from 1990 to 2011 (APC = −0.98, p < 0.05), followed by a notable increase from 2011 to 2021 (APC = 2.05, p < 0.05). For ASPR, a significant decrease occurred from 2001 to 2005 (APC = −4.80, p < 0.05), while subsequent periods showed an increasing trend, particularly between 2010 and 2018 (APC = 1.43, p < 0.05) and 2018–2021 (APC = 2.84, p < 0.05). In terms of age-standardized YLD rates (ASYR), China experienced an overall downward trend from 1990 to 2010 (APC = −0.56 for 1990–2001; −5.97 for 2001–2005; −1.01 for 2005–2010, p < 0.05), followed by a slight upward trend post-2010, with fluctuations from 2010 and 2018 (APC = 0.88) and 2018–2021 (APC = 2.49, p < 0.05). Age-period-cohort analysis showed that the risk of SCI incidence increased with age in China, though both period and cohort effects demonstrated a significant downward trend. Projections indicate that by 2036, the ASIR and ASPR for SCI in China will reach 6 and 146 cases per 100,000 people, respectively.ConclusionThe number and burden of SCI in China and globally have increased in the past. Among them, men and older people are more likely to develop SCI than women and younger people. Although the ASPR and ASIR for SCI are predicted to show a downward trend over the next 15 years, policy makers should continue to consider interventions to minimize the risk.